2022
DOI: 10.3389/fimmu.2022.817600
|View full text |Cite
|
Sign up to set email alerts
|

Ginsenoside Rg1 Alleviates Acute Ulcerative Colitis by Modulating Gut Microbiota and Microbial Tryptophan Metabolism

Abstract: Ulcerative colitis (UC) is a chronic and recurrent inflammatory disorder in the gastrointestinal tract. Here, we examined the pharmacological effects of ginsenoside Rg1, a natural compound with low bioavailability, on the acute experimental colitis mice induced by dextran sulfate sodium (DSS) and explored underlying mechanisms. Acute UC was induced in C57BL/6 mice by 2.5% DSS for 7 days, meanwhile, 2 mg/10 g b.w. ginsenoside Rg1 was administrated to treat the mice. Body weight, colon length, colon tissue patho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 73 publications
1
25
0
Order By: Relevance
“…Recent studies showed that Trp metabolism in the gut microbiota can be regulated by multiple factors such as natural substances and chemical drugs ( Figure 1 ). Ginsenoside Rg1 could increase the levels of Trp metabolites in the serum, including indole-3-carboxaldehyde, indole-3-lactic acid, 3-indolepropionic acid and niacinamide [ 43 ]. In mice with high-fat diet-induced obesity, ginsenoside Rb1 significantly altered the gut microbiota composition and serum Trp [ 44 ].…”
Section: Trp Metabolism In Gut Microbiotamentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies showed that Trp metabolism in the gut microbiota can be regulated by multiple factors such as natural substances and chemical drugs ( Figure 1 ). Ginsenoside Rg1 could increase the levels of Trp metabolites in the serum, including indole-3-carboxaldehyde, indole-3-lactic acid, 3-indolepropionic acid and niacinamide [ 43 ]. In mice with high-fat diet-induced obesity, ginsenoside Rb1 significantly altered the gut microbiota composition and serum Trp [ 44 ].…”
Section: Trp Metabolism In Gut Microbiotamentioning
confidence: 99%
“…The blockade of the kyn–AhR axis can ameliorate colitis-associated colon cancer through inhibiting the immune tolerance [ 169 ]. Multiple natural substances such as ginsenoside Rg1 [ 43 ], fucose [ 45 ], fuzhuan brick tea polysaccharide [ 48 ] and shenling baizhu san [ 51 ] could alleviate ulcerative colitis by modulating the gut microbiota and microbial Trp metabolism.…”
Section: Potential Application Of Gut Microbiota-derived Trp Metaboli...mentioning
confidence: 99%
“…In two IBD mouse models (DSS-induced and TNBS-induced), ginsenoside Rb1 could improve colitis by activating the endoplasmic reticulum-resident E3 ubiquitin ligase Hrd1 signaling pathway [ 16 ]. Not only that, ginsenoside Rg1 in ginseng can also regulate the intestinal microbiota of IBD mice to alleviate UC through microbial tryptophan metabolism [ 169 ]. Besides, ginsenoside Rh2 and ginsenoside Rk3 in ginseng have the same therapeutic and alleviating effects on experimental IBD [ 170 , 171 ].…”
Section: Nps With Ibd Therapeutic Activitymentioning
confidence: 99%
“…For example, the polyphenolic compound Salvianolic acid B could reduce the degree of inflammation in colitis by inhibiting the increase of Bacteroides and Akkermansia in the intestine of IBD mice [ 198 ]. Ginsenoside Rg1 significantly reversed the DSS-induced imbalance of intestinal microbiota in mice and attenuated acute UC symptoms through microbial tryptophan metabolism [ 169 ]. Juglone, a quinone, can increase the ratio of Firmicutes and Bacteroidota , increase the abundance of Actinobacteriota , and decrease the abundance of Verrucomicrobiota to alter the diversity and composition of intestinal microbes in UC mice [ 18 ].The coumarin-like compound daphnetin significantly increased the abundance of short-chain fatty acid-producing intestinal microbiota [ 253 ].…”
Section: Major Pathways Of Action Of Nps In the Treatment Of Ibdmentioning
confidence: 99%
“…AIS can cause disruption of the gut microbiota, which is an important cause of poor prognosis in AIS, and Traditional Chinese herbs can correct this microbiota disorder. It was found that the use of Chinese herbal preparations (both formulae and compounds) could restore the diversity of the gut microbiota to varying degrees, increase the abundance of probiotic bacteria, reduce the abundance of conditionally pathogenic bacteria, and bring the gut microbiota closer to that of healthy populations after AIS( Cai et al, 2019 ; Zhang et al, 2020 ; Fu et al, 2021 ; Lin et al, 2021 ; Wang et al, 2022b ; Cheng et al, 2022 ; Xu et al, 2022 ). To investigate how TCM regulates gut microbiota and how it exerts therapeutic effects, we searched for recently published studies on the regulation of gut microbiota by TCM in the treatment of AIS, including Chinese herbal formulae ( Table 1 ) and herbal compounds ( Table 2 ).…”
Section: Tcm Treats Ais By Interacting With the Gut Microbiotamentioning
confidence: 99%